Use of magnetic sand to improving writing ability for autistic children in special education laboratories - Reza Febri Abadi (JPK (Jurnal Pendidikan Khusus), 2020)
Abstract: This research is motivated by the availability of an autistic have not been able to write. One of the learning media that is assumed to be able to improve the writing ability of the child is magneticsand. The purpose of this research is to find out the use of magnetic sand to improve writing skills in children with autism. This research was an experiment by using the Single Subject Research (SSR) approach and A – B – A design was as the design of this research. The researcher collected the data by using observation and documentation and the data was analyzed by using in condition and among condition analysis. This research conducted in a month by 4 – 8- 4 (A1 – B – A2) section and by behavior target which made line shapes and vocal letters. The data was obtained on behavior target 1 was 40 % in baseline phase 1 (A1,) 80% in intervention phase, and 71,25 % in the baseline and behavior target 2 was 35 % in baseline phase 1 (A1,),  80 % in intervention phase and 71,25 % in the baseline. Thus, it can be concluded that the use of magnetic sand as a media can improve student’s writing ability.